Laminin 511 E8 fragment promotes to form basement membrane-like structure in human skin equivalents - Hitomi Fujisaki; Takafumi Watanabe; Shusuke Yoshihara; Hideki Fukuda; Yasuko Tomono; Chisa Tometsuka; Kazunori Mizuno; Toshio Nishiyama; Shunji Hattori (Regenerative Therapy)
Introduction: Laminin 511 (LM511), a component of the skin basement membrane (BM), is known to enhance the adhesion of some cell types and it has been reported to affect cell behavior. A recombinant fragment consisting of the integrin recognition site; E8 region of LM511 (511E8) has also been studied. 511E8 has been reported by many as a superior culture substrate. However, the effects of 511E8 on human skin cells remain unclear. In this study, we added 511E8 during the culture period of a reconstituted skin equivalent (SE) and investigated its effect on the formation of BM-like structures. Methods: SEs were formed by air-liquid culture of human foreskin keratinocytes (HFKs) on contracted type I collagen (Col-I) gels containing human fibroblasts. We compared the BM-like structures formed with and without 511E8 during HFKs culture periods. Morphological analysis, gene expression analysis of extracellular matrix components, and localization analysis of 511E8 in order to identify where 511E8 works were performed. Results: Immunohistochemical observation by light microscopy showed an accumulation of BM components between the gels and cell layers regardless of the addition of 511E8. There was a stronger and more continuous positive staining for LM α3, type IV collagen, and type VII collagen in the 511E8-added group compared to the no-added group. Transmission electron microscopic observation showed that the continuity of BM-like structures was increased with the addition of 511E8. Furthermore, gene expression analysis showed that the 511E8 addition increased some BM component genes expression, with collagen type IV and type VII α1 chains showing significant increases. His-tagged 511E8 was stained around the basal cells of HFK layers, not in basal regions. Co-staining with anti-His-tag and anti-integrin β1 antibodies revealed the co-localization of theses in some intercellular regions among basal cells. Conclusion: These results suggest that 511E8 effected on HFKs, enhancing the production of BM components and strengthening the anchoring between the Col-I gels and the HFK layers.